Knowledge, Awareness, Attitudes of Radiation Hazards and Protection Among Dentist: A Questionnaire Survey - Anuj Mishra; Kavleen K. Sethi; Sunita Srivastava; Rohit Mishra; Ayushi Tuteja; Ankita Dubey (Journal of Pharmacy and Bioallied Sciences)
Aim and Objective: To analyze the current status of knowledge, awareness, and attitude among the dentists toward radiation hazards and radiation protection. Materials and Method: The sample size collected for the study is 300 and those who fall under the inclusion criteria will be included in the study. A structured close-ended questionnaire will be designed to collect the data comprising of 16 questions related to the study. Results were analyzed using SPSS 20.0 (SPSS Inc., Chicago, IL). Results: The knowledge, attitude, and awareness about radiation protection were highest in dental interns followed by dental students, dental post graduate, and Private Clinic Dental Practitioners. Among the total participants, majority felt that lectures and workshops should be conducted to acquire knowledge on radiation hazards and protection. Conclusion: There is need “to fill” the knowledge deficit for students from both medical and dental fraternity thereby creating awareness about radiation hazards and protection. There is a need to educate current and future doctors regarding unnecessary exposure of individual to radiation.